2021
DOI: 10.1590/acb360307
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mild hypothermia plus rutin on the treatment of spinal cord injury and inflammatory factors by repressing TGF-β/smad pathway

Abstract: To probe the mechanism of mild hypothermia combined with rutin in the treatment of spinal cord injury (SCI). Methods: Thirty rats were randomized into the following groups: control, sham, model, mild hypothermia (MH), and mild hypothermia plus rutin (MH+Rutin). We used modified Allen's method to injure the spinal cord (T10) in rats, and then treated it with MH or/ and rutin immediately. BBB scores were performed on all rats. We used HE staining for observing the injured spinal cord tissue; ELISA for assaying T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…We believe that this effect may be attributed to the antioxidant, anti-inflammatory and osteogenic properties of the multilayer HA/CS-RT coating. Both rutin and chitosan have been suggested to alter multiple signalling pathways involved in osteogenesis and inflammation, including the BMP2/RUNX2, NRF-2/NF-κB, TGF-β/smad and PI3K/Akt signalling pathways [41,59,60]. However, more analysis of these signalling pathways is needed to elucidate the underlying molecular mechanisms leading to the effects seen in our study.…”
Section: Discussionmentioning
confidence: 94%
“…We believe that this effect may be attributed to the antioxidant, anti-inflammatory and osteogenic properties of the multilayer HA/CS-RT coating. Both rutin and chitosan have been suggested to alter multiple signalling pathways involved in osteogenesis and inflammation, including the BMP2/RUNX2, NRF-2/NF-κB, TGF-β/smad and PI3K/Akt signalling pathways [41,59,60]. However, more analysis of these signalling pathways is needed to elucidate the underlying molecular mechanisms leading to the effects seen in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Naringenin can exert neuroprotective effects by inducing neurotrophic factors and suppressing the apoptotic pathways ( Abbaszadeh et al, 2020 ). Rutin can repress the cellular inflammatory response after SCI through suppressing the activation of TGF-β/Smad pathway ( Yao et al, 2021 ). Luteolin can suppress oxidative stress and preserve mitochondrial function after SCI through signaling pathways involving Nrf2 activation and downstream gene expression ( Fu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sha et al demonstrated in a rat SCI model that apoptosis in SCI was mitigated by inhibiting the TGF‐β/Smad2 signaling pathway (Sha et al, 2017). Other studies have also shown that inhibiting the TGF‐β signaling pathway can reduce the cellular inflammatory response following SCI (Yao et al, 2021). In addition, it has a similar effect in other diseases.…”
Section: The Role Of Tgf‐β Signaling Pathway In the Pathogenesis Of Scimentioning
confidence: 96%
“…Flavonoids are widely found in natural plants, having the following properties of antioxidation, anti‐inflammation, anti‐tumor, and anti‐fibrosis (Wen et al, 2021). In both in vitro and in vivo models of SCI, myricetin (Lei, 2017), apigenin (Jin et al, 2022), and rutin (Yao et al, 2021) have been shown to inhibit inflammation or fibrous scarring by regulating the TGF‐β signaling pathway. Curcumin, which is a rhizome extracted in curcuma longa L, Inhibits TGF‐β Signaling Pathway to reduce glial scar formation (Yuan et al, 2019).…”
Section: Regulation Of Tgf‐β Signaling Pathway In Scimentioning
confidence: 99%